THE VALUATION OF THE RESIDUAL AND SECONDARY DEFORMATION OF THE MEDIUM FACE ZONE IN PATIENTS WITH UNILATERAL CLEFT LIP (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
The treatment of patients with cleft lip and palate is a complicated medical-social problem. The residual and secondary deformations of the nose, upper lip, and dentoalveolar require surgical correction in these patients after undergoing complete reconstruction as a child.